European Journals in the Social Sciences and Humanities - Heilbron, Johan; Bedecarré, Madeline; Timans, Rob (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
After a period of slow growth (1960–1985), journals in the social sciences and humanities which call themselves “European” have expanded rapidly. This process, which is related to the expansive European research and science policy, is shown to have occurred primarily in well-established (sub-)disciplines, and, secondarily, in more applied “studies” (educational sciences, management, urban studies, European studies) or in thematic domains (crime and security, health). Remarkably few “European” journals, however, have a multidisciplinary and innovative intellectual program; most are oriented toward mainstream approaches or have an ecumenical profile. European journals are published most frequently by Anglo-American publishers and edited by scholars from these countries. Countries of similar size and intellectual density like Germany and France lag very much behind the UK in this respect.